High‐Performance n‐Type Electrical Memory and Morphology‐Induced Memory‐Mode Tuning of a Well‐Defined Brush Polymer Bearing Perylene Diimide Moieties. (26th August 2015) - Kim, Young Yong; Ree, Brian J.; Kido, Makoto; Ko, Yong‐Gi; Ishige, Ryohei; Hirai, Tomoyasu; Wi, Dongwoo; Kim, Jehan; Kim, Won Jong; Takahara, Atsushi; Ree, Moonhor
<x xml:space="preserve">Abstract</x> Poly(N‐(1‐hexylheptyl)‐N′‐(12‐oxydodecyl)perylene‐3, 4, 9, 10‐tetracarboxyldiimide acrylate) (PAcPDI), a perylene diimide (PDI) containing brush polymer, is synthesized, revealing good solubility in organic solvents, excellent thermal stability up to around 340 °C, and two melting transitions over 130−220 °C. The self‐assembly and n‐type memory characteristics of PAcPDI in nanoscale thin films are quantitatively investigated. As‐cast films of PAcPDI are completely amorphous and the PDI units nevertheless formed π–π stacks favorably. However, the PAcPDI molecules can self‐assemble via thermal annealing, developing a well‐ordered horizontal lamellar structure with monomorphic or polymorphic monoclinic PDI crystals. The formation of monomorphic or polymorphic monoclinic crystals is attributed to various π–π stack modes of the PDI units, and is shown to be dependent on the film thickness. The differences in the thin film morphologies are directly reflected into the electrical memory behavior. The thermally annealed films demonstrate high‐performance n‐type unipolar volatile memory behavior within the thickness range of 12−31 nm. The as‐cast films show n‐type unipolar nonvolatile or volatile memory behavior in the range of 12−53 nm. The memory mode of PAcPDI films can be tuned by changing either the morphology or the film thickness.